Cover Image. Issue 1 (7th December 2021) - Doat, Olivier; Barboza, Bruno H; Batagin‐Neto, Augusto; Bégué, Didier; Hiorns, Roger C
Abstract : The cover image is based on the Review Review: materials and modelling for organic photovoltaic devices by Olivier Doat et al., https://doi.org/10.1002/pi.6280 . Abstract : The cover image is based on the Review Review: materials and modelling for organic photovoltaic devices by Olivier Doat et al., https://doi.org/10.1002/pi.6280 .